About user drawings of a psychiatric emergency (Research, Society and Development, 2024)
Among many ways of scrutinizing the human mind, drawing is one of the oldest and, therefore, valid for understanding subjectivity. Based on the clues that intramural art presents, it is up to health professionals looking for ways to dilute psychological suffering and help to stabilize the user. This study derived from an extension project carried out in a psychiatric emergency ward of a public hospital in Paraíba. Therefore, the objective of this manuscript is to reflect about drawings of users of that service. During many activities, a total of 219 foreshortenings were produced, including 160 pre-produced graphic works, 53 drawings by themselves, and 6 paper collages, coming from around 61 users. According to this result, it can be understood that drawings are a way for people to expose their personal stories, the history of the disease and also traces of psychopathological symptoms. It is up to mental health professionals, including psychologists, to create forms of management that direct users to psychosocial rehabilitation, using drawings as a basis for appropriate guidance.